2007
DOI: 10.1007/s00253-007-1153-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid production by recombinant Lactococcus lactis

Abstract: Microbial hyaluronic acid (HA), commonly produced by pathogenic Streptococcus, was made possible to be produced by a generally recognized as safe Lactococcus lactis by coexpressing HA synthase and uridine diphosphate-glucose dehydrogenase (UDP-GlcDH) of Streptococcus equi subsp. zooepidemicus in a nisin-controlled expression (NICE) system. With scarce expressed HA synthase alone, the constructed recombinant L. lactis (LL-NA) strain could produce HA with a concentration about 0.08 g/l in the M17 medium suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 19 publications
3
71
1
3
Order By: Relevance
“…As expected, an undersupply of UDPGlcA and UDP-GlcNAc decreased the yield. From these results, we can conclude that HasA is essential for HA production in L. lactis and improving the precursor sugar biosynthesis levels can increase the production of HA, confirming previous findings [4].…”
Section: Food-grade Ha Production In the Recombinant Strainssupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, an undersupply of UDPGlcA and UDP-GlcNAc decreased the yield. From these results, we can conclude that HasA is essential for HA production in L. lactis and improving the precursor sugar biosynthesis levels can increase the production of HA, confirming previous findings [4].…”
Section: Food-grade Ha Production In the Recombinant Strainssupporting
confidence: 91%
“…Several studies also showed that expressing endogenous UDP-GlcDH, which directs a step in the synthesis pathway of UDP-GlcA, could improve HA production [4,17,26]. We hypothesized that the endogenous enzymes involved in the synthesis of the UDP sugars should work more efficiently than the heterologous enzymes from S. zooepidemicus in L. lactis.…”
Section: Food-grade Ha Production In the Recombinant Strainsmentioning
confidence: 95%
“…HA has been produced in heterologous hosts, including Enterococcus faecalis (45), Escherichia coli (9,38), B. subtilis (46), and L. lactis (47). Given superior tools for strain engineering of the latter four hosts, it may prove easier to engineer microbial high molecular weight HA producers by targeting the UDP-GlcNAc/UDP-GlcUA ratio in these hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A produção de ácido hialurônico por Streptococcus é bastante conhecida, estando presente nas cápsulas das espécies Streptococcus thermophilus (IZAWA et al, 2009), Streptococcus pyogenes (KANG et al, 2012) e Streptococcus zooepidemicus (PATIL et al, 2011), além de Chlorella e Pasteurella multocida (DeANGELIS, 2012). Entretanto, a inserção de genes has que codificam para a enzima hialurona sintase, responsável por sua síntese, também foi eficiente para Bacillus subtilis (WIDNER et al, 2005) e Lactococcus lactis (CHIEN;LEE, 2007) produzirem esse polímero.…”
Section: Seleção De Bactérias Com Características De Rpcpunclassified